PEMBUATAN INSTRUMEN EVALUASI PEMBELAJARAN FISIKA MENGINTEGRASIKAN MSTBK BERBASIS ICT UNTUK MENGUKUR KOMPETENSI SISWA KELAS XI SEMESTER I - Aflah Zaharo; Akmam Akmam; Harman Amir (Universitas Negeri Padang, 2015)
Implementation of 2013 curriculum requires continuous and integrated evaluation instruments with the other sciences for learning. Generally, integrated and continuous evaluation instruments are not implemented in the school. One of solution that can be done to overcome this problem was to make the learning evaluation instruments with integrating MSTDC based on ICT. The purpose of this research was to determine the validity, description, practicality, and effectivity of learning material with integrating relevant knowledge and skills based on ICT. The kind of this research was research and development (R&D) with before-after experi ment design. Object of this research was learning material with integrating MSTDC based on ICT. The instru ments that used to collect data are validity sheet, practicality sheet, learning outcomes test sheet. There are two results of the data analysis. First, a description of the learning evaluation instrument integrates MSTDC based on ICT is valid with an average value of 93.6. Second, the use of learning evaluation instrument integrates MSTDC based on ICT in the assessment of learning outcomes is a practical physics characterized by the average value of the results of responses Physics teacher as a practitioner is 87.96 and the average value of student responses as well as the user is a 82.6 effective for used as an evaluation tool